In Hitler's Germany : everyday life in the Third Reich - Engelmann, Bernt, 1921-1994.; Engelmann, Bernt, 1921-1994. (New York : Schocken Books, 1988)
Ordinary citizens tell how it was to live in Germany during Nazi rule from Hitler's rise to power to the collapse of the Third Reich.
Translation of: Im Gleichschritt marsch and Bis alles in Scherben fällt.
The Roger Griffin ComFas Collection
Keywords: World War, 1939-1945 -- Germany; National socialism; Germany -- History -- 1933-1945.